PENGARUH PENERAPAN BUKU CERITA EMPAT KATA AJAIB TERHADAP SIKAP SOPAN SANTUN ANAK USIA 5-6 TAHUN - Wiranti, Wiranti; Suningsih, Taruni (Bunayya, 2025)
This study aims to determine the effect of the application of the four magic word story book on the politeness of children aged 5-6 years. The research method used is a quantitative pre-experimental method with a one-shot case study type. The research sample used 19 children aged 5-6 years consisting of 11 boys and 8 girls. In collecting data using observation techniques (checklist sheets) and tests (question items). The data analysis technique uses statistics with a t-test which obtains a value of t_(count) = 5.92 and a value of t_(table) = 1.734, which means Ha is accepted and Ho is rejected because t_(count) ≥ t_(table) namely 5.92 ≥ 1.734. The conclusion of this study states that the application of the four magic word story book has an effect on the politeness of children aged 5-6 years.